Design of Ring-Focus Elliptical Beam Reflector Antenna - Jun-Mo Wu; Xue Lei; Dong-fang Zhou; Lei Hou; Hong-wei Chen (International Journal of Antennas and Propagation)
A new method for the design of elliptical beam reflector antenna is presented in this paper. By means of the basic principles of ring-focus antenna, a circularly symmetric feed and two specially shaped reflectors are used to form an elliptical beam antenna. Firstly, the design process of this ring-focus elliptical beam antenna is studied in detail. Transition function is defined and used in the design process. Then, combining the needs of practical engineering, a ring-focus elliptical beam reflector antenna is manufactured and tested. The gain at center frequency (12 GHz) is 37.7 dBi with an aperture efficiency of 74.6%. 3 dB beam-width in φ=0° and φ=90° plane is 2.6° and 1.4°, respectively. Ratio of the elliptical beam (ratio of 3 dB beam-width in φ=0° and φ=90° plane) is 2.6/1.4=1.85, substantially equal to designed ratio 2. Simulating and testing results match well, which testify the effectiveness of this design method.